Research on Effective Teaching. A Multilevel Study for Ibero-America - Martínez-Garrido, Cynthia (2022)
This research aimed to determine the factors for Educational Effectiveness and to build an empirical model for Teaching Effectiveness in Ibero-America. A Multilevel Model with four levels of analysis was used to assess teaching effectiveness. The sample consisted of 5,722 students, (all at their third year of primary school), from 257 classrooms at 100 schools located in 9 countries of Ibero-America. The results showed the existence of ten factors of Teaching Effectiveness that impact on the cognitive, social, and emotional development of students: Involvement and commitment of the teacher; Classroom climate; High expectations and selfesteem; Structured lessons; Varied-participatory activities; Attention to diversity; Optimization of learning time; Classroom organization and management; Use of educational resources; Educational assessment, monitoring, and continuous feedback.